P-OT024. Stroke subtypes and in-hospital mortality in patients with systemic lupus erythematosus in dr. sardjito hospital yogyakarta - Damayanti, Ima; Setyopranoto, Ismail; Paryono; Darmawan, Anton (Clinical neurophysiology, 2021)
Introduction. Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder that associated with an increased risk of stroke especially in young patient. Individuals with SLE have a two-fold higher risk of stroke infarct and three-fold higher for intracerebral hemorrhage. Survival after stroke in SLE patient is lower compared to the general population. This study was conducted to determine the subtypes of stroke and in-hospital mortality in patients with SLE. Methods. A descriptive cross-sectional study. Subjects were SLE patients that had stroke and hospitalised at Dr. Sardjito Hospital from January 1st, 2015 until December 31st, 2019. Patients were diagnosed with SLE based on American College of Rheumatology Classification Criteria and stroke diagnosis was made by neurological examination and imaging finding (head CT scan/MRI). Results. All of the subjects were female with total 23 patients. The mean age was 33,65 (12,86) years old. There were 16 (69,6%) subjects having stroke infarct, 6 (26,1%) subjects having intracerebral hemorrhage and only one (4,3%) having subarachnoid hemorrhage. The most common subtypes of stroke infarct based on Oxfordshire Community Stroke Project (OCSP) classification was partial anterior circulation infarction (PACI) that was found in 11 (68,8%) subjects. In-hospital mortality was found in 10 (43,5%) subjects which 7 (30,4%) of them have had stroke infarct and 6 (26,0%) of them were categorized into age group below 40 years old. Conclusion. Subject in this study was female predominance. It was because SLE typically affects females rather than males. The most common subtypes of stroke was partial anterior circulation infarction. SLE could trigger the formation of blood clots that leads to inflammatory changes in blood vessels, which create a prothrombotic state, and increase risk of thromboembolism. In-hospital mortality was mostly found in stroke infarct and young subjects.